Наукові підходи до виховання толерантності зарубіжними дослідниками - Таргоній, Іванна (My University, 2019)
У статті розглядаються наукові підходи до виховання толерантності зарубіжними дослідниками. Особливої актуальності набуває вивчення зарубіжного досвіду виховання толерантності в молодого покоління, оскільки його творче використання сприяє пошуку ефективного виховання молоді в дусі толерантності. Виховання толерантності надає можливість пізнання культури різних народів, створюючи тим самим передумови взаєморозуміння і пошани, позиції співпраці, що є запорукою соціальної міжнаціональної стабільності. Основу сучасного освітнього простору має складати педагогіка толерантності, яка передбачає зміну системи людських відносин, побудову їх на взаємній повазі. Мета дослідження – розглянути підходи до виховання толерантності в молодого покоління у зарубіжному досвіді. Методи дослідження – теоретичні (аналіз, порівняння та зіставлення) – з метою вивчення літературних джерел, визначення термінологічно-понятійного апарату дослідження, узагальнення зарубіжного досвіду. Результати. Узагальнено змістову характеристику поняття толерантності як особистісної та професійної якості викладача, уточнено визначення основного поняття дослідження: «толерантність». The article deals with scientific approaches to the education of tolerance by foreign researchers. Particularly relevant is the study of foreign experience in the education of tolerance in the younger generation, since its creative use promotes the search for effective education of youth in the spirit of tolerance. The purpose of the study is to consider approaches to the education of tolerance in the younger generation in foreign experience.The problem of educating young people in tolerance as a moral feature of the individual is relevant, as in today's society, the spread of manifestations of discrimination, intolerance and disrespect to another point of view is relevant. Methods of research - theoretical (analysis, comparison and comparison) - with the aim of studying literary sources, definition of the terminology and conceptual apparatus of the study, generalization of foreign experience. Results. The content description of the concept of tolerance as a personal and professional quality of the teacher is generalized, the definition of the basic concept of the research is specified: "tolerance". The analysis of pedagogical research on the problem of education of tolerance in the younger generation suggests that the phenomenon of "tolerance" is viewed as: social and personal value, "as awareness of the person's need for a benevolent or restrained attitude to the differences between people in the broad sense, the avoidance of intolerance, the appreciation of diversity in nature, culture, religion, human relationships". Thus, in the basis of the definition of the phenomenon of "tolerance" there is a humanistic basis, a value relation to other people, the environment.
Keywords: толерантність; tolerance; види толерантності; виховання толерантності; педагогіка толерантності; зарубіжні дослідники; types of tolerance; education of tolerance; pedagogy of tolerance; foreign researchers